EFEK DARI LEVERAGE DAN UKURAN PERUSAHAAN DALAM MEMENGARUHI TINGKAT PROFITABILITAS - Rico Nur Ilham; Sarman Sinaga; Debi Eka Putri; Irada Sinta; Fuadi Fuadi (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the effect of Leverage and Firm Size on Profitability. This research was conducted on metal sub-sector companies and the like on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The sampling method used in this study is non-probability sampling with purposive sampling technique, namely by using specified criteria. Data collected through secondary data. The data used were tested with multiple linear regression data analysis techniques and hypothesis testing with SPSS version 21 as a tool. The results showed that leverage has a negative and insignificant effect on profitability, while firm size has a positive and insignificant effect on profitability. Companies are expected to be careful and take advantage of the use of high debt in the long term, because it can reduce profits for the company. Assets that are used as collateral are also considered to get debt whose value is greater than the return on assets received by the company. In order not to have a high risk of company bankruptcy. Keywords: Leverage, Firm Size, Profitability